(Istiḥdāmu Al-Ta'allum Al-Ilikteruniyyi fi Ta’allumi Al-Lughah Al-‘Arabiyyah lada al-Ṭullab fi Qismi Al- Lughah Al-Arabiyyah wa Adābiha fi Aṣnāi Wabāi Kūfid-19 Bil-Jāmi’ah Tulungagung Al-Islamiyyah Al-Ḥukumiyyah ) - Syafaah, Darisy SYAFAAH, (Faculty of Education and Teachers Training of UIN Sayyid Ali Rahmatullah Tulungagung, 2020)
One of the government policies in breaking the chain of spread of Covid 19 is the work from home (WFH) agenda, which in the world of education is realized through the application of online learning at all levels of education. At Tulungagung Islamic University, online learning in all study programs including the Arabic Language and Literature study program is carried out through an e-learning application managed by the Information rechnology center and database (TIPD) University. The Arabic Language and Literature Study Program it self is actually a study program where almost all of its courses use foreign language (Arabic), so it is not surprising that the teachers also have to take advantage of other learning technologies as support. The use of other media is an effort to achieve the goals of active language learning. This has become an attraction for researchers to find out and describe various forms of e-learning in the learning system of Arabic language courses in Arabic Language and Literature study program. The method used to explore and analyze data is descriptive qualitative method. The results showed that the online learning system (in network) in Arabic language material, the Lecturers in the Arabic Language and Literature Study Program make use of college training and combine it with other learning media such as video, youtube, ppt, kine master and by utilizing social media whatsaap. , zoom, and google meet.